2018
DOI: 10.3390/su10020424
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Tensions in Supply Chains: A Case Study of Paradoxes and Their Management

Abstract: Abstract:The comprehensive coverage of sustainability issues in a supply chain incurs goal conflicts-i.e., sustainability tensions-and is often limited by market characteristics, such as the availability of sustainable materials and services. While the mainstream business is prioritizing economic goals, a number of entrepreneurs are trying to move forward to more sustainable business practices for their own company and their supply chain. Fairphone represents such a case in the electronics industry, which is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 53 publications
(152 reference statements)
1
50
0
12
Order By: Relevance
“…Although managers of buying companies preferred to buy sustainable products or services, a lack of supplier capability and commercial requirements may discourage buyers from selecting the most suitable option—a sustainable product or service. This finding is consistent with prior studies by Brix‐Asala et al () and Font et al (), which reported a similar set of supply‐side (availability of sustainable materials and services) and demand‐side (disconnect between customer intention and purchase behaviour) supply chain sustainability tensions in the electronic supply chains. These studies identified several challenging situations that constrained managers from implementing SSCM practices.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although managers of buying companies preferred to buy sustainable products or services, a lack of supplier capability and commercial requirements may discourage buyers from selecting the most suitable option—a sustainable product or service. This finding is consistent with prior studies by Brix‐Asala et al () and Font et al (), which reported a similar set of supply‐side (availability of sustainable materials and services) and demand‐side (disconnect between customer intention and purchase behaviour) supply chain sustainability tensions in the electronic supply chains. These studies identified several challenging situations that constrained managers from implementing SSCM practices.…”
Section: Discussionsupporting
confidence: 92%
“…Hahn et al (, p. 299) went further to argue that “firms need to pursue sustainability aspects simultaneously—even if they seem to contradict each other.” Thus, it is important to recognize the inherent tensions that arise from reconciling normative and instrumental goals. By recognizing SSCM tensions between instrumental and normative stakeholder theory logics and carefully resolving the inherent tensions between such contrasting logics, an integrative stakeholder view enables sustainability and supply chain professionals to concurrently achieve contending yet desirable SSCM objectives (Brix‐Asala et al, ; Hahn, Figge, Pinkse, & Preuss, ). However, SSCM research has yet to thoroughly examine varied tensions present within supply chains (Xiao et al, ).…”
Section: Stakeholder Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Such activities are undertaken as part of global value chains and networks, in which the ties with remanufacturing and recycling firms are, so far, relatively weak. A notable development in this respect is the creation of the fair phone, which is innovatively using the demand side of its supply chain to drive sustainability [43].…”
Section: Policy Recommendations and Future Research Directionsmentioning
confidence: 99%